Compact Dual-Polarized Printed Slot Antenna - Li, Weiwen; Zeng, Zhijie; You, Baiqiang; Ye, Longfang; Liu, Yanhui; Liu, Qing Huo (IEEE antennas and wireless propagation letters, 2017)
A dual-polarized printed slot antenna is constructed by inserting the open-end slot into the coplanar waveguide center conductor of T-shaped slot. In order to verify the antenna performance, an antenna prototype was fabricated. The experimental results show that its working bandwidth is about 10.5%. In the operating frequency band, the isolation between two ports is higher than 27 dB. The proposed two-port antenna has bidirectional radiation characteristics, but the gain of the T-shaped slot element is higher than that of the open-end slot element. In the maximum radiation direction, the copolarization level of the T-shaped slot is 39 dB higher than the cross polarization and 30 dB for the open-end slot. The proposed dual-polarized antenna has a compact structure.